W „rezydencji” krakowskiego „Czasu” (1848–1934) - Bańdo, Adam (Rocznik Historii Prasy Polskiej, 2015)
W artykule przedstawiono dzieje redakcji „Czasu” w latach 1848-1934, gdy rezydowała ona w legendarnej siedzibie przy krakowskich Plantach, zburzonej w 1935 r. Omówiono również życie redakcyjne oraz kontakty redaktorów i współpracowników pisma z krakowską bohemą, w tym zaangażowanie redakcji w działalność kabaretu „Zielony Balonik”. [In the headquarters of the Cracow daily Czas (1848-1934)] The article recounts that phase (1848-1934) of the history of the renowned Cracow newspaper Czas [Time], when its editors had their headquarters at a former abbot’s palace at a corner of the Planty Gardens (in 1935, after they moved to Warsaw, the old mansion was torn down). The article deals in some detail with the life of editorial staff and freelancers, their contacts with the Cracow boheme, and especially their involvement in the activities of the literary cabaret The Green Balloon